INFORMATION TECHNOLOGY UTILIZATION AND ITS IMPACT ON SERVICE EFFECTIVENESS IN WEST JAKARTA - Pujiastuti, Nur Raisha; Triwinata, Jennie; Maryani, Dedeh (Universitas prof. Dr. Moestopo (Beragama), 2025)
The rapid advancement of information technology has significantly influenced the public service sector, including immigration services. This study examines the effect of information technology utilization on service effectiveness at the West Jakarta Immigration Office, with a particular focus on the role of employees in optimizing the